(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This paper analyzes the process of Islamization in the Batken region and examines the contributions of eshens, maksymys, and khojas to this process. It is well known that with the spread of Islam in the Fergana Valley, not only the religious beliefs of local peoples changed, but also their way of life and culture. Eshens, maksymys, and khojas, who are considered sacred and respected figures in Islamic society, were involved not only in spreading religion but also made a significant contribution to shaping the moral values and spiritual condition of the people. The study also examines major Islamic sacred sites in the Batken region and issues related to their history.